81.9k views
1 vote
Please help!

If we write
√(2) + (1)/(√(2)) + √(3) + (1)/(√(3)) in the form
(a √(2) + b √(3))/(c), such that
a,
b, and
c are positive integers and
c is as small as possible, then what is
a+b+c?

1 Answer

1 vote

Answer:


a+b+c=9+8+6=23

Explanation:

Let’s first simplify our expression. We have:


\displaystyle {\sqrt2+(1)/(\sqrt2)+\sqrt3+(1)/(√(3))

For the second term, multiply both the numerator and denominator by √2. This yields:


\displaystyle (1)/(√(2))\cdot(√(2))/(√(2))=(√(2))/(2)

Similarly, for the fourth term, multiply both the numerator and denominator by √3. This yields:


\displaystyle(1)/(√(3))\cdot(√(3))/(√(3))=(√(3))/(3)

Hence, our expression is now:


\displaystyle =√(2)+(√(2))/(2)+√(3)+(√(3))/(3)

Let’s combine them. First, we will need common denominators.

Our denominators are 2 and 3. So, our common denominator will be its LCM.

The LCM of 2 and 3 is 6.

Hence, let’s make each term’s denominator 6.

For the first term, we can multiply both layers by 6. Hence:


\displaystyle √(2)=(6√(2))/(6)

For the second term, we can multiply both layers by 3. Hence:


\displaystyle (√(2))/(2)=(3√(2))/(6)

For the third term, we can multiply both layers by 6. Hence:


\displaystyle √(3)=(6√(3))/(6)

And for the last term, we can multiply both layers by 2. Hence:


\displaystyle (√(3))/(3)=(2√(3))/(6)

So, our expression is:


\displaystyle =(6√(2))/(6)+(3√(2))/(6)+(6√(3))/(6)+(2√(3))/(6)

Add:


\displaystyle =(6√(2)+3√(2)+6√(3)+2√(3))/(6)

Combine like terms:


\displaystyle=(9√(2)+8√(3))/(6)

This cannot be simplified. So, c is as small as possible.

Hence: a=9, b=8, and c=6.

Therefore:


a+b+c=9+8+6=23

User Kike Gamboa
by
6.6k points